Noncontingent reinforcement as treatment for severe problem behavior: some procedural variations. - Lalli, J S (1997)
Noncontingent reinforcement (NCR) as a treatment for problem behavior has typically included (a) continuous access to reinforcers at the onset of treatment and (b) extinction. We extended research on NCR by conducting a three-phase preliminary investigation of these components. In Phase 1, a functional analysis showed that the problem behavior of 3 participants with developmental disabilities was maintained by tangible positive reinforcement. In Phase 2, treatment started with the initial NCR interval based on the latency to the first problem behavior during baseline. In Phase 3, treatment consisted of NCR without extinction to determine whether extinction was an essential treatment component. Results showed that the initial NCR schedule based on latency (Phase 2) and NCR without extinction (Phase 3) were effective for reducing rates of problem behavior compared with baseline. Findings are discussed regarding the initial schedule of reinforcement and extinction as components of NCR.